2002
DOI: 10.3354/meps242229
|View full text |Cite
|
Sign up to set email alerts
|

Fitness consequences of prey depletion for the common goby Pomatoschistus microps

Abstract: Pomatoschistus microps (Pisces: Gobiidae), a predatory, benthic feeder, occurs in high densities in variable, shallow, muddy coastal waters where prey availability can be unpredictable. Here, we investigate the effect and consequences of prey depletion on the body condition and nest building of adult male fish using manipulative mesocosm experiments in which the comparative value of meiofaunal and macrofaunal prey was investigated. Fish maintained in mesocosms from which macrofauna had been removed from the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In addition, Jackson et al (2002) concluded that a reduction in prey availability for P. microps reduced their condition and, consequently, their fitness and nest quality.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Jackson et al (2002) concluded that a reduction in prey availability for P. microps reduced their condition and, consequently, their fitness and nest quality.…”
Section: Discussionmentioning
confidence: 98%
“…Such measurements are indicators of tissue energy reserves and may characterize components of the environment in which the fish live (e.g. food and habitat availability, competition, predation, physical factors and pollution) (Jackson et al 2002;Copp 2003;Lloret & Planes 2003;Oliva-Paterna et al 2003). These measurements reflect what is generally known as fish condition.…”
Section: Introductionmentioning
confidence: 99%
“…, 2001) and positively with experimentally manipulated body condition (Kvarnemo et al. , 1998; Jackson et al. , 2002).…”
Section: Introductionmentioning
confidence: 96%
“…The somatic condition of individuals is an ecophysiological indicator widely used in the management of populations of fish (Jakob et al, 1996) because the tissue energy reserves in the individuals may characterize components of the environment in which the fish live (e.g., availability of food and habitat, competition, predation, physical factors, and pollution; Jackson et al, 2002;Copp, 2003;Lloret and Planes, 2003;Oliva-Paterna et al, 2003). Therefore, a low index of condition in fishes can negatively affect growth, survival, onset to maturity, and reproductive effort in subsequent phases of the life history of fish (Fechhelm et al, 1995;Rätz and Lloret, 2003;Hoey and McCormick, 2004;Morgan, 2004;Lloret et al, 2005).…”
mentioning
confidence: 99%